Penentuan Prioritas Pengambilan Pesanan Barang Oleh Angkutan Kota dengan Metode Rule-Based System - Rakhmawati, Nur Aini; Budi, Aditya Septa; Altetiko, Faizal Johan; Ramadhani, Fajar; Wardati, Nanda Kurnia; Hindrayani, Kartika Maulida (JSINBIS (Jurnal Sistem Informasi Bisnis), 2018)
Angkotin is a system that provides an alternative for urban transport to not only be used for passenger transportation, but also as freight service. Therefore, it needs a decision support system for taking order to delivery to the destination according to each criterion from urban transportation. The method used to develop this decision support system is a rule-based system. The result of this research is a decision support system that can help public transportation to find orders that can be taken based on four factors, such as distance, direction, route code, and status of storage capacity. Based on these four factors, the system can provide an order recommendation under the appropriate conditions through the Angkotin application. Based on our experiment, our system performs on 7 seven cases as expected.Â Â Â